2021
DOI: 10.3390/ijerph182312309
|View full text |Cite
|
Sign up to set email alerts
|

Externalities of Lean Implementation in Medical Laboratories. Process Optimization vs. Adaptation and Flexibility for the Future

Abstract: Important in testing services in medical laboratories is the creation of a flexible balance between quality-response time and minimizing the cost of the service. Beyond the different Lean methods implemented so far in the medical sector, each company can adapt the model according to its needs, each company has its own specifics and organizational culture, and Lean implementation will have a unique approach. Therefore, this paper aims to identify the concerns of specialists and laboratory medical services secto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
(97 reference statements)
0
8
0
1
Order By: Relevance
“…The study results are comparable with other studies, where a significant positive change in TAT was observed after initiating and implementing the Lean process throughout their laboratory. 2,5,6 However, the impact of the Lean Six Sigma on TAT was reduced due to the significant drop in the number of samples received post implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results are comparable with other studies, where a significant positive change in TAT was observed after initiating and implementing the Lean process throughout their laboratory. 2,5,6 However, the impact of the Lean Six Sigma on TAT was reduced due to the significant drop in the number of samples received post implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990s, the application of LSS in the manufacturing industry has come a long way. 1,2 Six Sigma is a quality management strategy that makes efforts to improve the quality of processes, utilizing the DMAIC process (Define, Measure, Analyze, Improve, and Control). 3 The "Lean" concept, on the other hand, is also a powerful quality-improvement tool that focuses on providing "value" and improving performance by systematically eliminating waste or non-value-added activities, from the process.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The demand continues to grow year on year both in volume and complexity as populations age and the healthcare becomes ever more sophisticated (Knowles and Barnes, 2013). They are expected to promptly deliver highly reliable data and results and give accurate input for timely disease diagnosis, prevention and health control (Apostu et al , 2021). To achieve this goal, laboratories must establish and maintain quality in all laboratory processes, while focusing on cost effectiveness (Inal et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies in pathology laboratories have generally focused on reducing errors, preventing wastage of motion and improving turnaround time (Zarbo and D’Angelo, 2007; Raab et al , 2008; Hayes et al , 2014; Sugianto et al , 2015). Turnaround time is one of the most significant measures of performance and quality for the pathology laboratory (Apostu et al , 2021). It is defined as the length of time from the moment a test is ordered or the specimen is received at the laboratory to the time when the result is reported to the clinician (Dey et al , 2013; Isack et al , 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Не зважаючи на наявність певних труднощів, зазначені переваги, дозволяють заглянути в майбутнє цифрової патології [16,19,20,27,28,32]. Тенденції управління цифровими даними в патології пов'язані з розвитком програмного та апаратного забезпечення цифровізації, зокрема інструментів аналізу зображень (збільшення пропускної здатності та зменшення варіативності), емуляції діагностичної процедури, управлінням значними об'ємами зображень високої роздільної здатності, взаємопов'язаними конвеєрами аналізу…”
Section: медична інформатика та інженеріяunclassified